Biological Impact of Recent Guidelines on Parenteral Nutrition in Preterm Infants. Issue 6 (December 2015) - Guellec, Isabelle; Gascoin, Géraldine; Beuchee, Alain; Boubred, Farid; Tourneux, Pierre; Ramful, Duksha; Zana-Taieb, Elodie; Baud, Olivier
ABSTRACT: Objectives: Recent guidelines for preterm neonates recommend early initiation of parenteral nutrition (PN) with high protein and relatively high caloric intake. This review considers whether these changes could influence homeostasis in very preterm infants during the first few postnatal weeks. Methods: This systematic review of relevant literature from searches of PubMed and recent guidelines was reviewed by investigators from several perinatal centers in France. Results: New recommendations for PN could be associated with metabolic acidosis via the increase in the amino acid ion gap, hyperchloremic acidosis, and ammonia acidosis. The introduction of high-intake amino acids soon after birth could induce hypophosphatemia and hypercalcemia, simulating a "repeat feeding–like syndrome" and could be prevented by the early intake of phosphorus, especially in preterm infants born after fetal growth restriction. Early high-dose amino acid infusions are relatively well tolerated in the preterm infant with regard to renal function. Additional studies, however, are warranted to determine markers of protein intolerance and to specify the optimal composition and amount of amino acid solutions. Conclusions: Optimal PN following new guidelines in very preterm infants, despite their demonstrated benefits on growth, may induce adverse effects on ionic homeostasis. Clinicians should implement appropriate monitoring to prevent and/or correct them.